Pathogenetic and clinical signifcance of EpCАM expression features in tumors and circulating tumor cells - V. M. Perelmuter; L. A. Tashireva; E. S. Grigoryeva; V. V. Alifanov; E. S. Pudova; A. V. Buzenkova; M. V. Zavyalova; N. V. Cherdyntseva (Сибирский онкологический журнал)
Purpose of the study: to summarize the available data on the structure and function of EpCAM and its domains, their roles in promoting proliferation and epithelial-mesenchymal transition (EMT), contributing to cell stemness, and facilitating interactions with cell adhesion and invasion molecules.Material and Methods. A comprehensive search was conducted for articles in Russian and English within the scientifc databases PubMed, Scopus, Web of Science, and E-library. A total of seventy-nine articles ranging from 1996 to 2024 were utilized to compile this review.Results. This review summarized the pathogenetic and clinical signifcance of various EpCAM expression variants: EpCAM^high, EpCAM^low, and EpCAM^loss. It described the causes and mechanisms behind the loss of membrane EpCAM expression, each holding distinct biological and clinical implications. Features of EpCAM expression in normal epithelial tissues, during regeneration, and in dysplasia/ neoplasia as well as carcinomas were carefully outlined. The clinical implications of EpCAM expression remain a subject of debate; overexpression of EpCAM has been linked to both unfavorable and favorable prognoses. Special emphasis was placed on the expression variants of EpCAM in circulating tumor cells, disseminated cells, and carcinoma metastases.Conclusion. The pathogenetic and clinical signifcance of EpCAM expression in various nosological forms of carcinoma is complex and multifaceted. Weak expression or absence of EpCAM acts as independent factors infuencing the unique progression patterns of these diseases. Achieving a deeper understanding of the role of EpCAM in disease progression necessitates the simultaneous examination of both its extracellular and intracellular domains.